GIS integrating local environmental knowledge in disaster preparedness community based landslide hazard mapping in Baguio City, Philippines - Winastu, Hendra (April 2009)
Landslides are one of the natural disasters that have a big effect on human lives, from the loss in the activities, investments, to the loss of life itself. Baguio City is known as the Summer Capital of the Philippines and is a landslide prone area because of its geologic and geographic setting. Provision of good information is needed as basis for a landslide risk management system to make the local people aware and lessen the adverse effects of natural occurrences in the future.
A landslide hazard map is produced to support a landslide risk management system together with local community perspective through a community-based mapping activity. It is a GIS supported integration of environmental knowledge in landslide hazard map creation and its joint evaluation by the local community and expert.
Environmental parameters such as topography, geological setting, vegetation cover, and proximity to the road network are considered for the creation of a landslide hazard map. Spatial-statistics method with logistic regression and linear regression formula was used for its creation. The results are evaluated based on the distribution of landslide inventory on the high probability landslide area and computation. Landslide hazard map from logistic regression using non landslide object with ranking system is found to be suitable for the study area. It point out that proximity to the end network with the value range 1-30m is the most influential parameter in the probability of landslide occurrences.
Community-based mapping showed the high risk area for the landslide occurrence. It also showed that major infrastructures are found within the high risk area. Spatial overlay is done to integrate this information with the researcher-created landslide hazard map. Joint-evaluation is made. The "common area" where community-delineated "high risk area" and researcher-delineated "high probability area for landslide" coincide can serve as starting point in building information for landslide risk management. Awareness of safer areas which are not located in the "high risk area" and "high probability landslide area" also serve as possible alternative evacuation or communication centers.
Thesis (MS Environmental Engineering)--University of the PHilippines Diliman
Keywords: Geographic information system